A Review on Electrochemical Sensors and Biosensors Used in Assessing Antioxidant Activity - Irina Georgiana Munteanu; Constantin Apetrei (MDPI AG, 2022)
Currently, there is growing interest in screening and quantifying antioxidants from biological samples in the quest for natural and effective antioxidants to combat free radical-related pathological complications. Antioxidants play an important role in human health and provide a defense against many diseases. Due to the valuable dietary role of these compounds, the analysis and determination of their amount in food is of particular importance. In recent years, many attempts have been made to provide simple, fast, and economical analytical approaches for the on-site detection and determination of antioxidant activity in food antioxidants. In this regard, electrochemical sensors and biosensors are considered promising tools for antioxidant research due to their high sensitivity, fast response time, and ease of miniaturization; thus, they are used in a variety of fields, including food analysis, drug screening, and toxicity research. Herein, we review the recent advances in sensors and biosensors for the detection of antioxidants, underlying principles, and emphasizing advantages, along with limitations regarding the ability to discriminate between the specific antioxidant or quantifying total antioxidant content. In this work, both direct and indirect methods for antioxidants detecting with electrochemical sensors and biosensors are analyzed in detail. This review aims to prove how electrochemical sensors and biosensors represent reliable alternatives to conventional methods for antioxidant analysis.